1998
DOI: 10.1021/jf980194q
|View full text |Cite
|
Sign up to set email alerts
|

Formation of N-(Carboxymethyl)fumonisin B1, Following the Reaction of Fumonisin B1 with Reducing Sugars

Abstract: The fumonisins are mycotoxins produced by fungi that contaminate primarily corn and are toxic through interruption of intracellular sphingolipid synthesis. Several reports have indicated that fumonisin B1 concentrations decreased when heated in aqueous solutions of reducing sugars. The incubation of fumonisin B1 with d-glucose resulted in the formation of N-(carboxymethyl)fumonisin B1, which was characterized by NMR and electrospray mass spectroscopy. We determined the methylene carbon of the carboxymethyl gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 36 publications
(43 reference statements)
2
84
0
3
Order By: Relevance
“…Only one product was observed from this reaction probably because the HPLC separated it from other potential nonenzymatic browning reaction products. The shorter reaction time (42) than that used here may have resulted in fewer reaction products in their reaction mixture. Poling et al (41) reported N-carboxymethyl-fumonisin B 1 as a secondary product from this reaction.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Only one product was observed from this reaction probably because the HPLC separated it from other potential nonenzymatic browning reaction products. The shorter reaction time (42) than that used here may have resulted in fewer reaction products in their reaction mixture. Poling et al (41) reported N-carboxymethyl-fumonisin B 1 as a secondary product from this reaction.…”
Section: Resultsmentioning
confidence: 95%
“…Poling et al (41) have identified this first product of fumonisin B 1 -glucose condensation as N-(deoxy-D-fructosyl-1-yl) fumonisin B 1 , the Amadori rearrangement product expected from glucose, with the same MW reported here. Howard et al (42) claimed that there was only one primary product, N-carboxymethyl-fumonisin B 1 , with a molecular weight of 779 when fumonisin B 1 reacted with D-glucose at 78°C for about 13 h. Their reaction products were separated with reversed-phase HPLC, and the HPLC column eluant was delivered to the mass spectrometer. Only one product was observed from this reaction probably because the HPLC separated it from other potential nonenzymatic browning reaction products.…”
Section: Resultsmentioning
confidence: 99%
“…The brown color of samples after extrusion suggested that loss of FB 1 might be due to the NEB reaction (21,22). The products of the FB 1 -glucose chain reaction were recently characterized as N-carboxymethylfumonisin B 1 (23,24) (24).…”
Section: Introductionmentioning
confidence: 99%
“…Fumonisins are also found to be relatively heat stable (Alberts et al, 1990;Howard et al, 1998) and light stable (IARC, 1993). They are also stable in stored products when these are kept in airtight at very low temperatures (Gelderblom et al, PROMEC Unit, Medical Research Council, Tygerberg, South Africa, 2002, unpublished data), or γ-irradiated .…”
Section: Fumonisins and Their Toxicological Effectsmentioning
confidence: 99%